MENINGKATKAN KEPERCAYAAN DIRI ANAK MELALUI “REWARD ASYIK” DI TK NEGERI PEDESAAN - Ayu Vera Dewi; Sri Watini (Jurnal Anak Bangsa, 2022)
Self-confidence is an important thing for early childhood to have, because having confidence will grow courage and increase children's enthusiasm to learn. Confidence is the ability of children to express feelings, be able to interact with others and dare to face life in the environment. At the Rural State Kindergarten, Walantaka District, Serang City, there are still some children who are not confident, such as lack of communication, not daring to express their feelings or opinions, not daring to answer the teacher's questions, being afraid and embarrassed to come to the front of the class. This research was conducted to increase the self-confidence of children aged 4-6 years in Rural State Kindergarten, Walantaka District, Serang City by using the "Reward Fun" Learning Model. Starting from a lack of confidence in children when they are playing. The “Reward Fun” learning method is a learning innovation developed by Sri Watini who has received a patent for a copyrighted work from the Ministry of Law and Human Rights of the Republic of Indonesia. In "Reward Fun" it is expected to be able to increase children's confidence in learning and playing, so that it will have a positive influence on the child which will continue to be felt throughout his life so that the child can develop optimally